Peer Relationship Process of Children of Divorced Parents in South Korea in the Early 2000s: A Qualitative Study - An, Hee-Lan (Journal of Ecohumanism, 2024)
This study explored the peer relationship process of children of divorced parents in South Korea in the early 2000s using in-depth interviews. The participants were 12 male and female adults who experienced parental divorce between 2002 and 2004. We identified three stages—incompatibility, sympathy, and ease—in their peer relationship process. The study shows the path through which the participants overcame their fear of self-disclosure and highlights implications that can be helpful in school counseling.